(untitled) (BRAC University Journal, 2026)
Since time immemorial, the necessity for hot water has been indispensable regardless of the advent of modem technology. In the dawn of the 21st century, only the means to heat the water has changed - now we mostly use electricity and gas in place of woods and other natural fuel. With that being said, lots of gas and electricity is being devoted to heat up the liquid for uses in hospitals, industries and households and the dernaod for hot water is ever climbing. Natural resources like fuel and coal are in liruited amouots and will not be able to sustain forever. Conseqoently, renewable energy is starting to gaio popularity in countries like Bangladesh. As a commitment to the development of the energy sector of Bangladesh, Control and Applications Research Centre (CARC) ofBRAC University has developed a Solar Hot Water System (SHWS) that would utilize solar energy to heat water, which could be used for several purposes like sterilization of medical equipment, cleaning of dishes, etc. An automated pilot project haa been implemented on the rooftop of BRAC University and research work haa been conducted for increasing the efficiency of the whole system by increasing the captured insolation and reducing wastage of heat overnight through insulation of the storage tank. With regard to procedural perspectives, this paper contemplates on highlighting the techoology implemented in the system and the improvisations made to elevate the efficiency and present a viable comparison between commercially available hot water systems with the developed automated uninterruptable SHWS.